PERAN MODAL SOSIAL DAN BUDAYA DALAM PERSPEKTIF PENDIDIKAN DI SEKOLAH DASAR NEGERI GUNUNG BUNDER 01 KABUPATEN BOGOR - Nurjanah, Siti; Nuraeni, Nunu; Hasanah, Tita (Prodi PGMI IAI Sahid, 2026)
This study aims to analyze the role of social capital and cultural capital in improving the quality of education at SDN Gunung Bunder 01, Bogor Regency. Social capital, which encompasses the network of relationships, norms, and trust between school members and the community, and cultural capital, consisting of inherited values, knowledge, and customs, are intangible but significant assets in supporting the educational process. This study used a qualitative approach with a case study method to explore the social and cultural dynamics within the school environment in depth. Data were collected through in-depth interviews with class teachers and fifth-grade student representatives, participant observation, and analysis of school documents. The results showed that utilizing social capital, such as school-community partnerships, voluntary parental involvement, and collaboration between teachers, can create a more supportive learning environment. Meanwhile, cultural capital manifested through the integration of local wisdom into the curriculum, the preservation of the value of mutual cooperation, and an appreciation of local traditions also strengthens students' learning motivation and encourages academic achievement. This study recommends the need for an educational development strategy based on local social and cultural potential as an effort to continuously improve the quality of education.